The Activity Test of Transdermal Patch Formulations From Ethanol Extract of Java Chili (Piper Retrofractum Vahl.) as an Analgesic in Male Mice - Luthfiyyah, Annisa; Elisma; Lestari, Uce; Naufal Nabillah Putra; Istiazah Putri Sisva; Johan Hasyim Nugroho; Aulia Tria Yustika (Chempublish Journal, 2025)
Pain is an unpleasant sensory and emotional experience caused by actual or potential tissue damage. Java chili (Piper retrofractum Vahl.) is an Indonesian plant known for its secondary metabolites, including piperine, pipernonalin, guineensine, and essential oils. Among these, piperine is the primary compound with potential analgesic properties. This study evaluates the analgesic effects of transdermal patches containing ethanol extract of Java chili using the writhing test and macrophage count in acetic acid-induced mice. The patches were formulated with different concentrations of the active ingredient: F1 (1g extract), F2 (2g extract), and F3 (3g extract). The results show that increasing the ethanol extract concentration significantly alters the physical characteristics of the patches, including shape, thickness, color, and durability. In the analgesic test, the macrophage count in the negative control group was 29.33 ± 0.57. In contrast, the treatment groups showed a concentration-dependent reduction: F1 (20.00 ± 1.73), F2 (13.00 ± 3.00), and F3 (7.33 ± 1.15). The positive control group exhibited the lowest macrophage count (3.66 ± 1.15). These findings indicate that transdermal patches containing Java chili ethanol extract possess significant analgesic potential, with higher concentrations yielding stronger effects.